(untitled) (Al-Qamar, 2021)
Plastic surgery is the branch of medicine in which the special operations are performed for the placement of organs and their functionalization. Plastic is derived from a Greek word plastickos which means moldings or giving a new shape. In all the ancient civilization of world where evidence about the ancient medicine and treatment are found there we also found evidence about the plastic surgery. According to historian in Hindustan this function was performed before two thousand years before Christ. In ancient Egypt the details about the surgery of faces are available as well as in first century before Christ in Roman medicine evidence about the simple technique about the surgery process are found. Firstly Hindustani doctors introduced this method of treatment then these translations reached Europe and they made full use of it. In 20th century in the field of plastic surgery an unusual development happened and came into being its different methods, purpose and shape. Generally western societies and especially in Muslim society the trend of plastic surgery is increasing. In fact now-a-days it is used as a fashion. In this situation the question is that what is point of view regarding this in Islamic Sharia. In Islamic law is this allowed or not? If it is allowed then in which situation. In the view of this need this article include research overview of the reality of plastic surgery, its purpose and different situation in Islamic perspective?